Implementation of Ki Hadjar Dewantara's Educational Philosophy Through Differentiated Learning In Pancasila and Civic Education for Junior High School Level - Septiwiharti, Dwi; Kulyawan, Roy; Dewi, Anjar Kusuma; Imran, Imran (Jurnal Mamangan, 2025)
The article discusses Indonesia's education system and its implementation of the "Merdeka" curriculum, based on Ki Hadjar Dewantara's educational philosophy. This philosophy emphasizes guiding children's natural abilities toward safety and happiness while considering the laws of nature and the laws of the times. Education should be adapted to children's needs within their cultural and evolving context. However, preliminary findings indicated that teachers, especially those teaching Pancasila and Civic Education, still encounter difficulties implementing differentiated learning approaches. The study examines how Ki Hajar Dewantara's educational principles are applied through differentiated learning in Pancasila and Civic Education at junior high schools in Palu City, focusing on developing appropriate modules. This qualitative study used observation, interviews, and documentation for data collection, followed by data analysis. The research analyzed teachers' understanding and implementation of these concepts. Results showed that junior high school teachers in Palu City who teach Pancasila and Civic Education understand differentiated learning principles but need improvement in a few areas, including differentiated worksheets for group students according to their learning readiness and styles